Energy meter system for gas-puff laser plasma - Bielecki, Zbigniew; Mikołajczyk, Janusz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
The authors demonstrate a detection system of EUV radiation pulses. The system provides energy measurements with uncertainty of 7.3% in the range of wavelengths 13.5 ± 0.5 nm (FWHM = 7.3%). The calibration of the system was taken using the E-Mon commercial meter and a laser-plasma source. The procedures made it possible to determine a calibration factor for the laser-plasma source with helium-xenon gas puff target. The factor is exploited for the purpose of standardizing measurements of EUV radiation with FWHM = 2%. A substantial improvement in the system responsivity is demonstrated.
Optica Applicata, Vol. 37, 2007, nr 1-2, s. 83-92
Keywords: optyka; EUV radiation; EUV energy meter; nanolithography